2013
DOI: 10.1002/ange.201210252
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Palladium(II) Reduction Pathways on the Structure and Activity of Palladium(0) Catalysts

Abstract: Am Scheideweg: Der Aktivierungsmechanismus von PdII‐Katalysatoren zur Bildung der aktiven {LnPd0}‐Spezies aus einer luftstabilen PdII‐Vorstufe wurde unter den Standardbedingungen der Miyaura‐Borylierung untersucht. Zwei Wege der Katalysatoraktivierung existieren unter diesen Bedingungen, die zu strukturell und chemisch verschiedenen {LnPd0}‐Komplexen führen (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Diboron compounds have proved to be an efficient mediator of various transformations by undergoing B−B bond cleavage. 1,2 The characteristic high oxophilicity of the boron center can facilitate energetically demanding transformations. With this understanding, we have successfully carried out a homogeneous palladium-catalyzed hydride transfer from water to reduce alkenes and alkynes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Diboron compounds have proved to be an efficient mediator of various transformations by undergoing B−B bond cleavage. 1,2 The characteristic high oxophilicity of the boron center can facilitate energetically demanding transformations. With this understanding, we have successfully carried out a homogeneous palladium-catalyzed hydride transfer from water to reduce alkenes and alkynes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In contrast, a very recent study involving [Pd(OAc) 2 -(PCy 3 ) 2 ] showed that this complex cannot be reduced to [Pd(PCy 3 ) 2 ] in the presence of an excess of PCy 3 , but follows a base-promoted pathway to form Cy 3 PO and a monophosphane-palladium(0) species, which is trapped in the presence of PhBr and water to form the dinuclear acetato-and hydroxo-bridged complex [{(Cy 3 P)Pd(Ph)} 2 (m-OAc)(m-OH)]. [24] To elucidate a possible mechanism for the palladium reduction by 4 and 5, the reaction of Pd(OAc) 2 with two equivalents of the phosphane ligand was monitored by NMR spectroscopy in [D 8 ]toluene solution. The 31 P NMR spectra showed rapid formation of the corresponding palladium(0) complexes with no indication of phosphane oxide formation, while the 1 H NMR spectrum showed characteristic multiplets in a 2:2:2:1 ratio at d = 6.54, 6.11, 5.22 and 2.03 ppm, which point to the formation of a cycloheptatriene species.…”
mentioning
confidence: 99%
“…Since the advent of Pd-catalyzed cross-coupling, simple Pd(II) sources such as halide and carboxylate salts have been the most common choice for in situ catalyst formation (Figure 1); however, multiple potential reduction pathways to generate active Pd(0) makes these systems more complex than they appear. [26][27][28][29][30][31] Other Pd(II) sources exploit the reactivity of allyl ligands to enable formation of metallated Pd(0) complexes in situ. CpPd(allyl) and CpPd(cinnamyl) are known to react with phosphines and generate Pd(0) via reductive elimination, 32,33 though this reactivity is ligand-specific.…”
Section: Introductionmentioning
confidence: 99%